2008
DOI: 10.1029/2007ja012631
|View full text |Cite
|
Sign up to set email alerts
|

The role of the tongue‐of‐ionization in the formation of the poleward wall of the main trough in the European post‐midnight sector

Abstract: [1] A series of radio tomography reconstructions from the University of Wales Aberystwyth receiver chains in Scandinavia and the UK, imaging the midnight-dawn sector on 13 December 2001, reveal a persistent large-scale electron density enhancement, which forms the poleward wall of the main ionization trough. Measurements by the European Incoherent Scatter radar (EISCAT) rule out in situ soft-particle precipitation as the main source of the higher densities. SuperDARN plasma drift observations and electric pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
(30 reference statements)
1
21
0
Order By: Relevance
“…The latitudinal location of the feature also compared well, although the model failed to reproduce the observed gradients on the walls of the enhancement, a likely consequence of the resolution of the model being lower than that of the tomography reconstruction. The model output in the study showed improvement over that obtained by Middleton et al (2008) who used a selected library potential pattern. There were only limited SuperDARN measurements at the time of the B z positive case, and an electric potential pattern from a different time period was used.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…The latitudinal location of the feature also compared well, although the model failed to reproduce the observed gradients on the walls of the enhancement, a likely consequence of the resolution of the model being lower than that of the tomography reconstruction. The model output in the study showed improvement over that obtained by Middleton et al (2008) who used a selected library potential pattern. There were only limited SuperDARN measurements at the time of the B z positive case, and an electric potential pattern from a different time period was used.…”
Section: Discussionmentioning
confidence: 73%
“…The two case studies with different IMF orientations were chosen to coincide with well-studied radiotomography investigations. The tomography results have already formed the focus of two previous works into the physical processes operating at high latitudes (Middleton et al, , 2008 where the observed features were interpreted by multi-instrument investigations. By choosing such cases, with mature interpretations of the data sets, ambiguity in the comparisons of observations with the model output was less likely.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations